(3QGMI GdCQhGM aj OaY YGgI GdCTHGMs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3GeG HYO adeG cGf OhQGf GdWGYhf Hjf GdfGS aCQOJ Cf CcJH QSGdI Jchf TGajg ddOGA JQjGbkG ddWGYhf hGdhHGA s
(3BNQgG (B:s
(3HYO Cf jfbY ai eGA GhQO hjHd hjTQH hSde ef GdWGYhf HEPf Gddg s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B99 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B268 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs